Replacement of wybutine by hydrazines and its effect on the active conformation of yeast tRNAPhe. - Schleich, H G (1978)
The highly modified base wybutine (YWye) next to the anticodon of yeast tRNAPhe has been replaced by different hydrazine derivatives. The effect of the replacement on the activity of the tRNA has been studied in the heterologous aminoacylation with synthetase from E. coli and in the poly(U) directed binding to ribosomes from both yeast and E. coli. It was found that starting from tRNA-PheYWye the activity increased with increasing size, aromaticity, and stacking tendency of the substituent replacing YWye. It is concluded that YWye by the size of its aromatic system and by its stacking properties is particularly well suited for stabilizing the native conformation of tRNAPhe.